2022
DOI: 10.1007/s11258-022-01284-z
|View full text |Cite
|
Sign up to set email alerts
|

Native and invasive bunchgrasses have different responses to trail disturbance on California coastal prairies

Abstract: Ecosystems often experience small-scale disturbances through recreational foot and bike traffic. The intermediate disturbance hypothesis predicts that frequent disturbances in grasslands can negatively impact native species and lead to invasion by disturbance-adapted, non-native species. Disturbance studies often examine intentional or unintended larger scale disturbances, but do not commonly focus on common small-scale disturbances such as those caused by trampling along trails. As such, we were interested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Another major impact of human disturbance, including trampling, is promoting the survival and spread of invasive species in plant communities by the unintentional introduction of seeds carried on clothes and shoes, as well as the intentional introduction of non-natives for ornamental or other purposes [54,55]. Exacerbating this issue is that non-native species can outperform native species in trampled habitats [54,[56][57][58]. However, there is limited data to corroborate such findings for alpine ecosystems.…”
Section: Future Researchmentioning
confidence: 99%
“…Another major impact of human disturbance, including trampling, is promoting the survival and spread of invasive species in plant communities by the unintentional introduction of seeds carried on clothes and shoes, as well as the intentional introduction of non-natives for ornamental or other purposes [54,55]. Exacerbating this issue is that non-native species can outperform native species in trampled habitats [54,[56][57][58]. However, there is limited data to corroborate such findings for alpine ecosystems.…”
Section: Future Researchmentioning
confidence: 99%
“…In the study area, annual roadside maintenance involves soil disturbance, removal of native vegetation, and periodic plowing and mowing on roadsides (Ramirez Brumatti 2016, Chiuffo et al 2018b). This disturbance typically reaches a relatively short distance from the road, usually less than 20 m. We referred to non‐disturbed communities as those growing in areas adjacent to disturbed communities that are in general less affected by humans and dominated by native vegetation (McDougall et al 2018, Luong et al 2023). The reserve does not experience any other major anthropogenic disturbance, and although cattle are not present, it maintains a substantial population of Cervus elaphus (Hierro and Cock 2013, Estanga‐Mollica et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…those events that cause the partial or total destruction of vegetation (sensu Grime 1977), enhances plant invasion is common in ecology (Hierro et al 2006, Moles et al 2012). Disturbance can facilitate plant invasion by reducing competitors and consumers and releasing resources (Davis et al 2000, Pearson et al 2014a, Luong et al 2023). Accordingly, many studies have reported an increase in non‐native basal area (Bellingham et al 2005), biomass (Domènech and Vilà 2006), cover and density (Hierro et al 2006), establishment (Burke and Grime 1996), survival (Domènech and Vilà 2006, De Villalobos et al 2011) and richness (Deutschewitz et al 2003, Sharma and Raghubanshi 2009, Paiaro et al 2011) with disturbance.…”
Section: Introductionmentioning
confidence: 99%